BENEFITS OF USING SGLT2 INHIBITORS IN THE TREATMENT OF HEART FAILURE: A LITERATURE REVIEW - Nogueira Jales, Davi; almeida, Maria Clara Barbosa de; kronbauer, Cinobelina Pinheiro Elvas; Damasceno Júnior, Evandro César Bezerra; Aguiar, Sheylla Raquel Diniz Cavalcante; sampaio, Janaína Mendes Caldas; Silva, Emília Moura; Gonçalves, Ysa Bruna Araújo; Hellmann, Loara Oliveira; Landim Filho, Paulo Henrique Paes; Carvalho, Ana Sophia do Amaral Simões (Brazilian Journal of Implantology and Health Sciences, 2024)
This review article addresses the benefit of the use of SLGT2 inhibitors in patients with heart failure, a chronic and complex pathology associated with several comorbidities. The objective is to analyze the efficacy of pharmacological therapy with the use of SLGT2 inhibitors, considering the benefits both in the control and progression of the disease and in hospitalizations and mortality With regard to the results and discussion of this article, SLGT2 inhibitors have been shown to be effective in reducing the risk of cardiovascular death or hospitalization for heart failure. In addition to offering the benefit of reducing oxidative stress and slows down the progression of kidney disease caused by hyperglycemia, especially in diabetic patients, which contributes to an improvement in the cardiovascular outcomes of these patients. . In addition to offering the benefit of reducing oxidative stress and slows down the progression of kidney disease caused by hyperglycemia, especially in diabetic patients, which contributes to an improvement in the cardiovascular outcomes of these patients. Studies have shown that these drugs play a significant role in reducing the risk of hospitalizations due to heart failure, consolidating themselves as an essential therapeutic strategy in the prevention of new cases of this condition.